Religion and Peace in the Middle East - Mumtaz Ahmad (International Institute of Islamic Thought, 1989)
This slim volume is based on the three papers presented at the Council for the World’s Religions (CWR) conference on “Interreligious Dialogue and Peace in the Middle East” held in Toledo, Spain in March 1988. The conference was intended to discuss the role of religion in the pursuit of peace in the Middle East. The volume begins with a paper on “Religion and Politics: Dangers and Possibilities for Peace in the Middle East” by Rabbi David J. Goldberg. Goldberg argues that the on going Arab-Israeli conflict is essentially political and not religious in its origin, its cause, and in the perception of those most intimately involved. Hence, the resolution of conflict could only come from a concerted effort to find an acceptable and mutually beneficial geo-political hrmula which seeks to accommodate the just demands and needs of both parties. Any attempt to seek a solution only in “apocalyptic terms” would undoubtedly lead to more conflicts and wars. Goldberg claims that religious differences did not originally loom large as a source of conflict in the Middle East. This may be true before 1967. But since the Israeli occupation of El-Quds, the religious dimension of the Arab-Israeli conflict has become equally, if not more, important than the political dimension. For Muslims throughout the world, the constant reminder that one of the three holiest places in their religious tradition is out of their reach cuts a deep psychological wound. Rabbi Goldberg believes that common to the three monotheistic faiths of the Middle East are “certain shared principles” that govern ethical behavior, recognize the rights of other people, and determine responsibilities of governments. The logic of acknowledging and re-affirming these shared principles may open new possibilities of conflict resolution and mutual understanding. Goldberg states: “As a Jew, therefore, I have no hesitation in asserting that the Palestinian right to self-determination is just as valid as my insistence on Jewish self-determination.” Farhang Rajaee’s paper on “Religion and Politics in Islam: The Iranian Context” is an important attempt to understand “the internal logic” of Islam with regard to religion and politics or the relations between the secular and the sacred. Rajaee argues that the aim of politics in Islam is identified with religion. Seeing Islam as a systematic whole implies that “the distinction and separation between various aspects of life make little sense.” Politics, ...